2020
DOI: 10.1186/s13047-020-00402-2
|View full text |Cite
|
Sign up to set email alerts
|

Development and evaluation of a dual density insole for people standing for long periods of time at work

Abstract: Background: Appropriate footwear is important for those who stand for prolonged periods of time at work, enabling them to remain comfortable, healthy and safe. Preferences for different footwear cushioning or hardness are often person specific and one shoe or insole will not be the choice for all. The aim of this study was to develop a range of insole options to maintain comfort during long periods of standing at work and test insole material preferences in the workplace. Methods: The study consisted of two pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 45 publications
1
19
0
2
Order By: Relevance
“…More dynamic conditions that increase forefoot plantar loading could reveal differences in perceived comfort, such as running (Yang et al, 2019;Hennig et al, 1996), fatigue (Biseaux and Moretti, 2008), faster walking (Burnfield et al, 2004;Castro et al, 2015) or a greater load (Pau et al, 2015). In addition, insole materials which further increase to the relative midfoot contact area and pressure may also be subjectively perceived as more comfortable (Anderson et al, 2020;Wintana et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More dynamic conditions that increase forefoot plantar loading could reveal differences in perceived comfort, such as running (Yang et al, 2019;Hennig et al, 1996), fatigue (Biseaux and Moretti, 2008), faster walking (Burnfield et al, 2004;Castro et al, 2015) or a greater load (Pau et al, 2015). In addition, insole materials which further increase to the relative midfoot contact area and pressure may also be subjectively perceived as more comfortable (Anderson et al, 2020;Wintana et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…However, the effect might reduce over prolonged use, whilst alternative elastomers may retain their properties for longer (Saraswathy et al, 2009). Perceived comfort also changes over a longer wear time due to both material insole and foot properties (Anderson et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Four studies have evaluated associations between foot characteristics and comfort, specifically addressing foot alignment [ 14 , 78 , 104 ] and tactile sensitivity [ 81 ]. In relation to arch height, Zifchock et al [ 104 ] compared comfort ratings while wearing custom and semi-custom orthoses, and found that participants with high arches reported greater arch and heel comfort in the semi-custom device which provided less rearfoot control when walking, while Anderson et al [ 14 ] assessed perceptions of nine different insoles which varied according to the hardness of the heel, midfoot and forefoot in participants working in occupations that require prolonged standing, and found that those with lower arched feet preferred insoles with harder material in the midfoot. Miller et al [ 78 ] compared comfort perceptions when walking and running in three shoes that varied in relation to stiffness, cushioning and shape, and found that heel eversion angle was negatively associated with comfort in the stiffer, harder soled shoe.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, a redesign of the arch pad shape according to the anthropometric data and foot features of the target population is one of the possible ways to improve discomfort in the arch and midfoot area. In addition, the overall preference may be affected by many factors, such as movement, fit, and density (Anderson et al, 2020; Wang et al, 2020). This might explain the slight discomfort in the arch and midfoot area, although the IPS had the highest overall preference rating.…”
Section: Discussionmentioning
confidence: 99%